P347Physician-led, weight loss advice prior to atrial fibrillation ablation, overall weight change and clinical outcomes. (18th June 2020) - Lau, Y; Mackey, W; Connelly, D
Abstract: Background: Randomised trial, controlled study and international guidelines have advocated weight loss in AF patients with obesity as a means of attaining better AF burden control and maintenance of sinus rhythm. However, previous study required patients to undertake a highly structured weight management programme, detailed counselling, meal plans and behaviour modification. Aim: To assess if weight-loss can be attained through a 5-minute, target-driven, physician-led counselling amongst overweight/obese patients referred AF ablation, without the need for intensive weight management programme. Subsequently to assess this can lead to better clinical outcomes (reduction in AF recurrence and readmission). Methods: All patients referred for AF ablation in a tertiary centre over a 6-month period were included. Baseline weight and BMI at initial encounter plus weight and BMI at day of AF ablation were recorded. Optional physician-led counselling was provided, with aim for target weight loss of <10% or reduction of 3 point in BMI. Initial contact to AF ablation is 6 months. Clinical outcomes such as symptomatic AF >3 months post AF ablation and readmission for symptomatic AF were recorded. Follow-up duration of 6 months post ablation. Patients received counselling were designated Group 1, and those who did not were designated Group 2. Outcomes: 146 new AF referrals for ablation seen over the 6-month period. 105 (71.9%) are paroxysmal AF, 37 (25.3%) are persistent, 4 permanent AF. Mean BMI 34.4 (+/- 5.1). Out of which, 76% have BMI > 30 (Obese), 47.6% possess BMI >35 (Morbidly obese), with 1 patient with BMI exceeding 50. 21.9% patients received physician-led counselling to lose weight. Basic demographics (age, gender), proportion of pAF and duration of AF, use of antiarrhythmic drugs were not statistically different between the two groups. Among AF patients receiving weight-loss counselling (Group 1), they have higher mean weight and BMI, 108kg (+/- 14.3) and BMI 33.7 (+/-4.3), as compared to those who did not received counselling (Group 2), 87.5kg (+/- 16.2) and BMI 29.5 (+/-4.3). At point of AF ablation, Group 1 has median weight loss of (-)4.5kg, mean reduction of BMI (-)2.0 points, while Group 2 has median weight gain of 3.6kg, increase of BMI 1.1 point. Overall statistically significant difference in weight change (p <0.001). Composite clinical outcomes at 6 months post ablation comprising recurrence of AF and readmission for symptomatic AF were higher in Group 2 as compared to Group 1, 38% vs 13% (p = 0.03). Summary: This small cohort study suggests that concise physician-led weight loss counselling (without dietician-led meal plan or extensive weight loss programme) provided to AF patients with increased BMI can lead to significant weight loss and lower BMI in the run-up to AF ablation. This is also associated with statistically significant reduction in recurrence of AF and hospital re-admission.